Evaluative prenominal possessives in Spanish - Eguren, Luis (Borealis – An International Journal of Hispanic Linguistics, 2018)
In this paper, the properties of Spanish evaluative prenominal possessives (i.e. the affective possessive preceding a proper name, the so-called “emphatic possessive”, and the possessive in the Old and American Spanish doubled possessive construction) are thoroughly described, and compared with those of canonical prenominal possessives. It is mainly proposed that evaluative possessives, in contrast to canonical prenominal possessives, are not base-generated as nominal modifiers and then raise to D0, but are directly merged (mostly) within the DP domain, thus capturing the fact that affective, emphatic and doubling possessives just evaluate the relation between the possessum and the possessor, and are not interpreted as complements of the noun. In order to account for their different distribution, it is further argued that the three types of Spanish evaluative prenominal possessives are inserted (basically) in different structural positions in an split-DP.